2019
DOI: 10.12998/wjcc.v7.i18.2787
|View full text |Cite
|
Sign up to set email alerts
|

Giant squamous cell carcinoma of the gallbladder: A case report

Abstract: BACKGROUNDGallbladder cancer is the most common malignant tumor of the biliary tract. The majority of cases are adenocarcinoma. Squamous cell carcinoma is the histological type present in 12% of all neoplasias accounting for approximately 12% of gallbladder neoplasms. It can occur in its pure form reaching 1%-3% of the tumors. Many patients are at an advanced stage when diagnosed and have bad therapeutic efficacy.CASE SUMMARYA 45-year-old male patient presented with left flank pain for 1 year and irradiated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Giant gallbladders are associated with various obstructions of the cystic duct of the bile duct, such as stones, parasites, or tumors. [1,7,8] There are also sporadic reports of gallbladder neck gangliocytopenia leading to dilated gallbladder. [6] In this patient, there was no cystic duct obstruction or any other underlying disease.…”
Section: Discussionmentioning
confidence: 99%
“…Giant gallbladders are associated with various obstructions of the cystic duct of the bile duct, such as stones, parasites, or tumors. [1,7,8] There are also sporadic reports of gallbladder neck gangliocytopenia leading to dilated gallbladder. [6] In this patient, there was no cystic duct obstruction or any other underlying disease.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestation of gallbladder cancer is frequently ambiguous or delayed in comparison with the pathologic progression, which leads to advanced staging and a poor prognosis at the time of diagnosis [1] , [10] , [11] . The majority of patients present to the hospital with a vague upper abdominal pain or a palpable tumor on physical examination; this may be an accidental discovery on imaging or a histological finding [12] , [13] . Jaundice, abdominal lump, anorexia, and weight loss are frequent signs of advanced stages.…”
Section: Discussionmentioning
confidence: 99%
“…Chapman et al reported a 10 × 6.5 × 0.5 cm papillary, circumferential tumor located primarily in the body and neck of the 18 cm large gallbladder and Hsu et al reported a 16.4 × 13.6 × 7.8 cm GB with poorly differentiated adenocarcinoma [ 22 , 24 ]. Junior et al reported a case of giant squamous cell carcinoma of gall bladder infiltrating the transverse colon, however the size was not mentioned [ 26 ]. Based on the sizes mentioned in indexed literature, it appears that our case is the largest resectable GBC reported till date.…”
Section: Discussionmentioning
confidence: 99%